2016
DOI: 10.4103/0253-7613.194859
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal aspiration of bleomycin: An alternative experimental model of pulmonary fibrosis developed in Swiss mice

Abstract: Objective:Pulmonary fibrosis (PF) is a progressive and predominantly lethal form of several interstitial lung diseases with limited current therapeutics; it is, therefore, essential to develop a simple, homogeneous, and noninvasive disease model to investigate possible anti-fibrotic approaches. The present study is designed to develop oropharyngeal aspiration (OPA) model of bleomycin (BLM)-induced PF as a simple and alternative to intratracheal (IT) administration of BLM in Swiss mice strain.Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Bronchoalveolar lavage fluid was collected thrice from each animal by passing 1 mL of ice-cold PBS into the trachea, followed by gentle aspiration of the fluid by inserting a catheter in the trachea ( Bale et al, 2016 ). The percentage recovery of lavage fluid was approximately 85% and did not differ among the animal groups significantly.…”
Section: Methodsmentioning
confidence: 99%
“…Bronchoalveolar lavage fluid was collected thrice from each animal by passing 1 mL of ice-cold PBS into the trachea, followed by gentle aspiration of the fluid by inserting a catheter in the trachea ( Bale et al, 2016 ). The percentage recovery of lavage fluid was approximately 85% and did not differ among the animal groups significantly.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the IT delivery of BLM through a microspray aerosolizer ( 8 ) has been shown to yield more reproducible results and more homogenous distribution of fibrotic lesions than IT instillation/injection ( 9 ). Following the example of other drugs and agents ( 10 13 ), an alternative way of administering BLM in the trachea, namely oropharyngeal aspiration (OA), has been recently introduced ( 14 , 15 ). However, the IT and OA routes of BLM administration have not been directly compared ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, these techniques require technical expertise and anesthetization of animals prior to administration, and repeated dosing may cause inflammation and injury to the trachea. An alternative technique to IT installation and tracheostomy is oropharyngeal aspiration, which can potentially overcome some of the challenges mentioned above [ 23 , 24 , 31 ]. Lakatos et al compared oropharyngeal aspiration to IT instillation to establish a silica-induced fibrosis mouse model and observed that administration of silica particles by aspiration resulted in a more uniform pulmonary distribution with minimal intra-animal variability [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Price et al recently discussed in detail the importance of animal model selection when evaluating an inhaled product in the preclinical stage [ 20 ]. Most of the published papers evaluating inhaled drugs employ small animal models such as mice and rats due to ease of availability, affordability, and handling [ 3 , 7 , 22 , 23 , 24 ]. In this study, we evaluated three widely reported preclinical inhalation (direct) techniques: the MicroSprayer ® Aerosolizer (Penn-Century, Wyndmoor, PA, USA; recently discontinued), the BioLite Intubation System (Braintree Scientific, Braintree, MA, USA), and oropharyngeal aspiration.…”
Section: Introductionmentioning
confidence: 99%